Use substitution to solve the system of equations 1/24/2014 | Leslie from Cedar Lake, IN | 2 Answers | 0 Votes Mark favorite Subscribe Comment
x=2y+7 equation 1 x=y+4 y=x-4 equation 2 substitute the value of y in equation 1 x=2(x-4)+7 x=2x-8+7 x=2x-1 x=1 substitute the value of x in equation 2 y=1-4 y=-3 1/24/2014 | Shelly J. Comment
Substitute x from first equation into second 2y + 7 = y + 4 y = 4 - 7 = -3 Substitute value of y into first equation x = 2(-3) + 7 x = -6 + 7 = 1 :) 1/24/2014 | Amarjeet K. Comment